Recurrent vulvovaginal candidiasis in Colombian women: Main clinical and microbiological characteristics (2023)
ABSTRACT: Vulvovaginal candidiasis (VVC) is the second cause associated with genital tract infections; Approximately 75% of the female population will suffer from VVC at least once in their life (1,2). It is estimated that 138 million people worldwide have recurrent vulvovaginal candidiasis (RVVC), which is defined as four or more episodes of VVC in one year (3,4). This condition is mainly caused by C. albicans, although an increase in other species has been reported. Among the different risk factors associated with the development of RVVC, the following are described: pregnancy, use of therapy with broad-spectrum antibiotics and steroids, hormone replacement therapy, genetic mechanisms, immune (HIV, uncontrolled diabetes and other underlying diseases) and some hygiene, behavioral and idiopathic habits. A failure in the natural or primary immune response is also considered a predisposing factor for suffering RVVC, when the patient does not present any of the aforementioned factors (5).